GAMBARAN KADAR KOLESTEROL PADA PEMINUM KOPI DI KELURAHAN TELUK AIR KECAMATAN KARIMUN - Mega Pratiwi Irawan; Dwinur Aini; Eli Yusrita (LPPM Universitas Abdurrab, 2022)
Coffee is a drink with a very high polyphenol content. The polyphenols in coffee are very rich in caffeoylquinic acids, feruloyquinic acids, and dicaffeoylquinic acids. The most abundant polyphenolic compound in coffee is cholorogenic acid. Based on the results of research conducted by respondents, coffee consumption in the long term can increase cholesterol levels in the body. The purpose of this study was to determine cholesterol levels in coffee drinkers in the Teluk Air sub-district, Karimun District. This type of research is using a descriptive method that provides an objective picture. The results showed that of the 30 respondents, respondents who were female with high results were 8 respondents and normal respondents were 7 respondents, respondents who were male with high results were 7 respondents and normal results were 8 respondents.